KNOWLEDGE AND PRACTICE OF BREAST SELF EXAMINATION AMONG ANTENATAL ATTENDEES PRESENTING TO A TERTIARY CARE HOSPITAL IN KARACHI, PAKISTAN - Tazeem Shahbaz; Khair un Nisa (Journal of University Medical & Dental College, 2013)
ABSTRACT Background: Breast cancer is considered to be a disease of both the developing as well as developed countries and diagnosis can be made at an early stage by using breast self-examination (BSE). Objective: To assess knowledge and practice of breast self examination among antenatal attendees presenting to a tertiary care hospital Methods: This cross-sectional study was conducted at Outpatient Department of Gynecology and Obstetrics at Jinnah Postgraduate Medical Centre, Karachi, from 15th January, 2010 to 20th October, 2010. One hundred and fifty females presenting as antenatal attendees (excluding those with breast complaints) were selected and interviewed. Pre tested, structured questionnaire, containing (open and closed ended) questions, along with demographic profile was used to gather data which was analyzed using SPSS. Results: Mean age of participants was 28.3 years with range of 15-50 years. Majority were educated (78.7%) with average of matric education. The mean duration of marriage was less than five years; Most were Muslims (92%), and Urdu speaking (66.7%) with average of 2 children and livings in a joint family. Most of the respondents (80.0%), had heard of breast cancer and breast self-examination. Twenty three percent knew the early symptoms of breast cancer and 83.3%% knew that early detection increases chances of survival. Nine percent of the respondents gave the view that breast self-examination should start at less than 19 years while 15.3% said that it should start after 19 years of age and 76% don’t know about it at all. The respondents also gave opinion that breast self-examination should be performed (weekly (13.9 %), some monthly (76.3%) and some yearly (9.8%). Most of the respondents (66.7%) are of the opinion that BSE can be performed at any time in the month while 16.7% have view that it should be done on every fifth day of menses with another 16.7% attendees who don’t know its timing. One hundred and thirty two (88.0%) of the antenatal attendees don’t know about the breast self-examination while 18 (12.0%), knew about it. The level of awareness of breast self examination was highest (29.0%) among those aged 15-29 years and was lowest among those more than 30 years (p = 0.064). (Table2). The women who had secondary education had more knowledge about breast self-examination while those who had primary education had low level of knowledge. (p = 0.069). ) Among the participants who had knowledge about BSE, (15.3%) knew the exact age to start for BSE,(66.7.0%) responded that it can be carried out at any time during a month, only 16.7.0% said that it should be done during menses. Ninety four percent knew that BSE can be done with their own hands with out any help. Fifty four percent do it during bath and 33.3% while lying on a bed. Similarly, 66.7% had knowledge that a lump can be found during exam along with 5.6% looking for color change in skin of breast and 27.8% can expect both the signs. Conclusion: Most of the antenatal attendees had very poor knowledge, and almost no practices of BSE